A comparative analysis of the data management and archiving practices of scientific agencies PAGASA, PHIVOLCS and the Manila Observatory - Samaniego, Carina C.; Gonzales, Grace Marie B.; Rey, Emma M.; Arlante, Salvacion M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2008)
The field of science is fast changing and a number of studies, such as climate change and natural disasters, can be addressed if there is a complete set of data where researches will be based upon. The volume of scientific data in various formats is growing exponentially. Observed data provide a baseline for determining rates of change and for computing the frequency of occurrence of unusual events, such as El Nino, volcanic activities, earthquakes, typhoons, etc. These are not only useful in predicting future natural and geotectonic events but also in creating a map of the past and its relation to the future.
This study focused on the data management and archiving practices of three (3) major scientific agencies here in the Philippines. The Philippine Atmospheric Geophysical Astronomical Service Administration (PAGASA) is the official agency in the field of meteorology, operational hydrology, climatology, astronomy and other allied sciences. The Philippine Institute of Volcanology and Seismology (PHILVOLCS) predicts the occurrence of volcanic eruptions and earthquakes and other geotectonic. The Manila Observatory is a private, non-stock, non-profit research institution that deals with climate change assistance, regional climate systems modelling and other related sciences.
Specifically, this study aimed to: 1. Describe the system of data collection, organization, dissemination and preservation of PAGASA, PHILVOLCS, and the Manila Observatory. 2. Illustrate extent have these agencies developed their data management and archival system to be able to meet their roles and programs 3. Describe data management and archiving practices and policies common among these agencies. 4. Illustrate how the scientific nature of these agencies effect the management of their data. 5. List comments and suggestions.
The case study method of research was used which involved interviews, collection analysis and examination of the data management and archiving process of each agency. The study showed that these agencies hold significant scientific data that are useful in developing scientific awareness and national environmental security. It also showed that there is a need to review and establish an effective data management and archiving of these scientific agencies. These agencies face the same issues and challenges that most scientific institutions have in terms of data management and archiving: natural threats; financial, professional skills and technological limitations; lack of weak archiving programs and systems; conflicting priorities; and differences in management systems. It is recommended that each public and private scientific agency evaluate their current data management systems and to build a consortium of scientific agencies where data management and archiving can be improved and supported.
Vita.
Thesis (Master of Library and Information Science)
Keywords: Records -- Management -- Philippines -- Quezon City; Science -- Philippines -- Data processing; Administrative agencies -- Science -- Philippines -- Data processing